Dysfunctional Bronchial Cilia Are a Feature of Chronic Obstructive Pulmonary Disease (COPD). (2nd November 2021) - Thomas, Biju; Koh, Mariko Siyue; O'Callaghan, Christopher; Allen, John Carson; Rutman, Andrew; Hirst, Robert Anthony; Connolly, John; Low, Su Ying; Thun How, Ong; Chian Min, Loo; Lim, Wan Teck; Lin Ean Oon, Lynette; et al.
Abstract: Impaired mucociliary clearance may increase COPD exacerbation risk. We aimed to compare bronchial ciliary function and epithelial ultrastructure of COPD patients to healthy controls and explore its relationship to exacerbator phenotypes (frequent [FE] and infrequent [IFE] exacerbator). In this cross-sectional study, 16 COPD patients and 12 controls underwent bronchial brushings. Ciliary beat frequency (CBF) and dyskinesia index (DI; % of dyskinetic cilia) were assessed using digital high-speed video microscopy, and epithelial ultrastructure using transmission electron microscopy (TEM). Bronchial epithelium in COPD showed lower CBF and higher DI, compared to controls (median [IQR] CBF: 6.8 (6.1–7.2) Hz vs 8.5 (7.7–8.9) Hz, p <0.001 and DI: 73.8 (60.7–89.8) % vs 14.5 (11.2–16.9) %, p <0.001, respectively). This was true for FE and IFE phenotypes of COPD, which were similar in terms of bronchial CBF or DI. Subgroup analyses demonstrated lower CBF and higher DI in FE and IFE COPD phenotypes compared to controls, irrespective of smoking status. TEM showed more loss of cilia, extrusion of cells, cytoplasmic blebs and dead cells in COPD patients versus controls. Profound dysfunction of bronchial cilia is a feature of COPD irrespective of exacerbation phenotype and smoking status, which is likely to contribute to poor mucus clearance in COPD. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.1963695 .